Kualitas Kishk Yang Dibuat Dari Campuran Yogurt Dan Tepung Sagu (Metroxylon sp) - Nurliyani, Nurliyani (2013)
Kishk is a fermented milk product from the Middle East that is traditionally made from a mixture of yogurt, wheat flour and salt with sun drying. This study aimed to determine the quality of kishk made from a mixture of yogurt and sago flour with the addition of 6% sugar (sucrose) during storage at room temperature. Yogurt made from pasteurized milk using starter Lactobacillus bulgaricus and Streptococcus thermophilus, with the addition of 0 and 6% sugar and fermented at a temperature of 42о C for 6 hours. Kishk dough made by adding one part sago flour that has been roasted and 4 parts of yogurt. The mix was fermented for 24 hours at a temperature of 37о C, moulded in sphere-shaped flat and dried in an oven at a temperature of 50° C for 48 hours. Each treatment stored for 0; 21 and 42 days at room temperature with three replications. Quality evaluation of kishk includes microbiological quality (total lactic acid bacteria) and chemical quality (lactose content, acidity, pH, moisture content). The data were statistically analyzed by two way ANOVA. The results showed that the addition of sugar as much as 6% have no effect on the kishk quality during storage, with an average total lactic acid bacteria was 6.32 log CFU / g, 2.59% of lactose, 2.30% acidity, pH value was 3.69 and 10.39% of moisture content. In conclusion, kishk made from sago flour mixed with yogurt and sugar addition of 6% can be stored at room temperature for 42 days without decreasing in quality.